MOLECULAR PHYLOGENY OF SECTION DROSANTHE (SPACH) ENDL. (HYPERICUM L.)INFERRED FROM CHLOROPLAST GENOME - Dogan, Gulden; Yilmaz, Asli; Bagci, Eyup; Kaya, Zeki (Pakistan Botanical Soc, 2017)
The phylogenetic relationships of Drosanthe section of Hypericum genus (Hypericaceae) were analyzed by using non-coding chloroplast DNA region (trnL 3'-trnF) for 58 individuals. The section is represented by 23 taxa and nine of which are endemic to Turkey. The chloroplast phylogeny suggested that the members of this section belonged to a polyphyletic group, which imply at least two independent origins. The individuals of this section clearly formed two main clades. One clade included all members of this section except H amblysepalum, H. spectabile, H. lysimachioides var. spathulatum and H. sorgerae. Our current phylogenetic results supported the morphological grouping in the Drosanthe section.
Keywords: Hypericum; Drosanthe; Chloroplast DNA; trnL 3 '-trnF region; Polyphyletic